Risk Factors of Young-Onset Colorectal Cancer: Analysis of a Large Population-Based Registry - Daneshvar Danial; El Douaihy Youssef; Bayat Mokhtari Maryam; Abureesh Mohammad; Bayat Mokhtari Moein; Deeb Liliane (Canadian Journal of Gastroenterology and Hepatology)
Background. As the third most common type of cancer in the United States, colorectal cancer (CRC) was previously thought to be rare in young populations. Despite a decrease in the overall incidence of CRC, the rate of new cases under 50 years old has been continuously increasing. Aim. The purpose of our study was to analyze risk factors of young-onset CRC. Methods. Commercially available software platform, Explorys, was used to extract data from a collective healthcare database electronically. Results. In this database, 13,800 young adults (age 20–50) were diagnosed with primary colorectal malignancy. Compared to subjects with a previous family history of CRC who had an odds ratio of 17.78, those diagnosed with primary malignant neoplasm of breast and inflammatory bowel disease (ulcerative colitis and Crohn’s) had odds ratios of 16.94, 4.4, and 3.7 for young-onset CRC, respectively. Patients with a history of alcohol abuse, smoking, obesity, diabetes mellitus, and hyperlipidemia had higher chances of developing young-onset CRC. In addition, the odds of CRC were lower in Hispanic ethnicity in comparison to Caucasians (OR: 0.54), with no statically significant differences between Caucasian, African American, and Asian populations. Conclusion. Currently, this is an expansive study investigating the risk factors for early-onset CRC. The analysis showed factors such as family and individual history of IBD to have high association with early onset. Notably, an individual history of breast malignancy was strongly associated with early-onset CRC.